Self-assessment as an Autonomous Learning Tool in an Interpretation Classroom - Lee, Yun-Hyang (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis paper explores the usefulness of self-assessment in an interpretation classroom. Students of the Korean-English Program in a two-year graduate school of translation and interpretation were asked to analyze and assess their interpretation performances and submit a self-assessment report to the instructor. Later, a survey was conducted to find out what aspects of self-assessment the students found positive or negative. Based on the responses of the student and the teacher, selfassessment was found to be positive in identifying students’ weaknesses and strengths, enable targeted practice, and allow them to monitor their own progresses. But students also found selfassessment to be time-consuming and emotionally draining. However, all students and the instructor agreed that self-assessment was conducive to students. learning in an interpretation classroom.